Paris and the marginalized author : treachery, alienation, queerness, and exile - Orlando, Valérie, 1963-; Pears, Pamela A., 1971- (After the empire., 2019)
"This volume explores what it is that has brought marginalized writers together by way of Paris. Spanning from the inter-war period to the present millennium, we consider the questions that have influenced and continue to shape the realm of exiled writers who have sought refuge in Paris in order to write"--